The Australian environment - Brown, A.G.; Turnbull, J.W.; Booth, T.H. (1997)
The volume is designed to provide a reference text for all those concerned with selecting and growing trees and shrubs in rural areas of developing countries and in the more tropical parts of Australia. The purpose of this first chapter is to provide an introduction to the main features of the Australian environment within which the trees and shrubs described in the book have evolved. Emphasis is on those factors of the environment for which data are likely to be available in field situations in other countries where Australian trees and shrubs might be used, so facilitating the initial selection of species through the use of homoclimes. Such information has much more predictive value than observed natural occurrence, which can be limited by various factors such as fire and competition, which in turn may change, and gives no indication of adaptability or plasticity of potentially useful species. As moisture availability and temperature are very important influences on the survival and growth of plants, this chapter concentrates on these factors.